Intergenerational Differences in Communication Processes with the Homeland: Turkish Immigrants Living in Australia - Duygu Tosunay Gencelli (Journal of Economy Culture and Society)
The focus of this study is the first-generation Turkish immigrants who went to Australia to work after the bilateral agreement signed between Australia and Turkey in 1968 and their second and third generation relatives. The objective is to reveal the communication processes of different generations of Turkish immigrants living in Australia with Turkey in terms of transnationalism. The research was designed as a holistic single case study in accordance with the qualitative method. Accordingly, triangulation was ensured by using data collection tools such as online observation, semi-structured interviews and participant observation. The field research was carried out in Sydney, Australia between September 2018 and January 2019. During the research, semi-structured interviews were held with 30 participants who were reached by snowball sampling. Of the 30 participants, 14 are from the first generation, 13 are from the second generation and 3 are from the third generation. Findings show that the means of communication and engagement with their homeland, which have evolved significantly since the beginning of Turkish immigration to Australia, directly affected the migrants' lives. Additionally, it has been observed that transnational ties are strengthened by thechoice of communication tools that provide instant communication. It was also revealed that the developing technology and historical conditions had different effects on different generations of migrants.